QOL-34. The relationship between Psychological Flexibility, Quality-of-Life and psychological health in young people who have experienced a brain tumour. (3rd June 2022) - Airdrie, Jac; Geagan, Chloe; Davies, Nicholas; Powers, Katie; Wright, Ingram; Borrill, Heather; Gibson, Faith; Clifford, Steve; Lowis, Stephen; Bailey, Simon; Limond, Jennifer; Owen, Ray; et al.
Abstract: Despite increasing survival rates in young people who have experienced a brain tumour, this patient group have the poorest reported quality-of-life (QoL) of all cancer survivors. QoL is defined as an individual's perception of their position in life in relation to their goals, expectations and standards. QoL can be influenced by physical functioning but one of its strongest predictors is psychological health. A concept that has a large impact on psychological health is Psychological Flexibility (PF). PF refers to the ability to recognise and adapt to situations, shift cognitive and behavioural repertoires which are impacting negatively on personal and social functioning and commit to behaviours that are in line with strongly held values. Studies have demonstrated a relationship between PF and QoL in other patient populations such as chronic pain and breast cancer survivors. In this study we explored the relationship between PF and QoL at baseline in a sample of young people enrolled in a randomised controlled trial of Acceptance and Commitment Therapy (ACT) for young people who have experienced a brain tumour. We found that higher PF was associated with higher QoL in both 11-15 year olds (R2 = .69, p < .05) and 16 – 24 year olds (R2 = .29, p < .01). We also found higher PF was associated with lower levels of mental health difficulties (R2s ≥ .24, ps < .01) which was also associated with higher levels of QoL (R2 = .49, p < .01). The results suggest assessing and providing support to increase PF is important for young people who have experienced a brain tumour. It highlights that interventions found to increase PF, such as ACT, could be helpful in improving psychological health in this population.